Pembuatan Abstrak Informatif Laporan Penelitian Koleksi Layanan Deposit Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Nur, Devi Nofrida; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
The purpose of this study is to describe the making of informative abstracts of research reports collection service deposit Archives and Library Service of West Sumatra Province to make it easier to find the information needed at any time. The method used in writing this paper is a descriptive method with data collection techniques through direct observation. Stages in making informative abstracts are; (1) read and collect documents; (2) abstract recordings; (3) making and typing informative abstract; (4) examination of the abstract final manuscript; (5) the use of the index, in this informative abstract also made index, the index listed on the informative abstract is the first index of the author, both the title index and the three keyword indexes. Informative abstracts are made to facilitate users in finding information and users do not need to read the entire contents of the research report collection Service Deposit Archive Service and Library of West Sumatra Province.Keyword: abstract informative; collection; research report